THE ANALYSIS INTERNET MARKETING IMPLEMENTATION AS ONE OF MARKETING MEDIA AT THE PATRA BALI RESORT & VILLAS - Ni Kadek Risna Noviandari; I Nyoman Rajin Aryana; I Putu Astawa (Politeknik Negeri Bali, 2018)
Internet marketing is very important to support marketing activities in the current era of technology. The purpose of this study, to find out how the implementation of marketing media through internet marketing used along with the revenue generated and to determine which variables are most effective in increasing the occupancy rate of rooms in The Patra Bali Resort & Villas. The study results show that internet marketing used are; websites, online travel agents (OTA), social media and e-mail. Hotel website and online travel agent give direct contribution to room occupancy and hotel’s revenue. Social Media (facebook, twitter, instagram, tripadvisor) and e-mail don’t contribute directly because they are just as communication’s tools. Online travel agent gives the highest contribution to the increasing room occupancy than hotel website. The total of 3 years contributions from 2015-2017, online travel agent contribute 18,83% with the higest income from booking.com 7.6%. Hotel website contribute 2.42%. Internet marketing’s income is increasing and decreasing in certain months due to the holiday peak season. This study have an impact for development internet marketing media used as the basis for taking decision at The Patra Bali Resort & Villas hotel, in an effort to increase rooms occupancy and achieved the sales target through internet marketing set by hotel management.